Lack of a significant adverse cardiovascular effect of combined quinine and mefloquine therapy for uncomplicated malaria. - Supanaranond, W; Suputtamongkol, Y; Davis, T; Pukrittayakamee, S; Teja-Isavadharm, P; Webster, H; White, N (1997)
Quinine dihydrochloride (10 mg salt/kg infused over one hour) and mefloquine (15 mg base/kg) were given simultaneously to 13 adults with uncomplicated falciparum malaria. Supine and standing blood pressures were recorded and the electrocardiogram monitored. Plasma concentrations of the 2 drugs were similar to those reported previously for the 2 compounds given individually to a similar group of patients. Although postural hypotension was common (6 cases before treatment and 7 after) and the electrocardiogram QTc interval was prolonged by a mean of 12% (SD = 8) following drug treatment, there was no evidence of a clinically significant cardiovascular pharmacodynamic interaction between these 2 structurally related antimalarial compounds.